2019
DOI: 10.1016/j.toxrep.2019.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Acute oral toxicity evaluation of extracts of Hydrocotyle sibthorpioides in wister albino rats as per OECD 425 TG

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…So, Dunaliella salina powdered will preserve kidney function through normalization of urea and creatinine levels. This may be linked to the antioxidant properties of Dunaliella; since ROS may be implicated in the Glomerular Filtration Rate (GFR) impaired [[20], [21], [22]]. The increase in Hb level, which detected in the present study may be attributed to the B-carotene is considered as a precursor of vitamin A and a single oxygen quencher, so could affect the immune system through both pathways of antioxidant and retinoid [23].…”
Section: Discussionmentioning
confidence: 80%
“…So, Dunaliella salina powdered will preserve kidney function through normalization of urea and creatinine levels. This may be linked to the antioxidant properties of Dunaliella; since ROS may be implicated in the Glomerular Filtration Rate (GFR) impaired [[20], [21], [22]]. The increase in Hb level, which detected in the present study may be attributed to the B-carotene is considered as a precursor of vitamin A and a single oxygen quencher, so could affect the immune system through both pathways of antioxidant and retinoid [23].…”
Section: Discussionmentioning
confidence: 80%
“…Measurement of haematological parameters plays is crucial in assessing the physiological and pathological status in man and animals. Thus alteration in normal values of these parameters could occur following ingestion of some toxic plants [ 28 , 29 ]. In the sub-chronic study for 28 days, no significant alteration was observed in all the haematological parameters of the treated rats when compared with the control group except for group treated with the fraction of leaf ethyl acetate of the plant at 750 mg/kg that had significantly (P < 0.05) higher values of neutrophil, basophil, eosinophil, monocyte and lymphocyte compares to control group rats.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed transaminase serum enzymes ALT & AST start releasing from the cytosol and translocate into the bloodstream, leading to mild or severe liver injury (Figueredo et al 2018;Hazarika et al 2019;Ramaiah 2011). In our study, LA did not elevate these transaminase enzymes, considering nontoxic nature of LA at different dose levels.…”
Section: Discussionmentioning
confidence: 49%